2020
DOI: 10.3390/nu12061545
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Comparison of the Impact of ‘Warning’ and ‘Health Star Rating’ FoP Labels on Adolescents’ Choice of Breakfast Cereals in New Zealand

Abstract: This research investigated the performance of the red, octagonal Vienna Convention traffic ‘STOP’ sign as a front of pack (FoP) warning nutritional label. While the Vienna Convention traffic light system is an established FoP label, the potential of the ‘STOP’ sign in the role has not been investigated. The performance of the ‘STOP’ label was compared with that of a single star (low nutritional value) Australasian Health Star Rating (HSR) label using a fractionally replicated Latin square design. The labels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
3
11
1
Order By: Relevance
“…Our results differ from other similar experimental studies, including some with children and adolescents, that have found that WLs usually dissuade consumers from purchasing foods high in critical nutrients and help in the identification of the healthiest products [5]. For example, a study with adolescents (16-18 years) in New Zealand found that the presence of octagon WLs significantly reduced the intention to purchase breakfast cereals of low nutritional value [26]. In Uruguay, a study involving children from 8 to 13 years found that two designs of WLs (the traffic light system and octagons) reduced the choice of products high in critical nutrients [15].…”
Section: Discussioncontrasting
confidence: 99%
“…Our results differ from other similar experimental studies, including some with children and adolescents, that have found that WLs usually dissuade consumers from purchasing foods high in critical nutrients and help in the identification of the healthiest products [5]. For example, a study with adolescents (16-18 years) in New Zealand found that the presence of octagon WLs significantly reduced the intention to purchase breakfast cereals of low nutritional value [26]. In Uruguay, a study involving children from 8 to 13 years found that two designs of WLs (the traffic light system and octagons) reduced the choice of products high in critical nutrients [15].…”
Section: Discussioncontrasting
confidence: 99%
“…This is highlighted when FOPL understandability is not reflected in consumer choice, as in Fialon et al [39] and Vandevijvere S. [53]: they studied respectively a sample of Italian and Belgian subjects, and the Nutri-Score was found to be the best in helping consumer to categorize foods, but it was not associated with a shift in food choices between food categories. The same result was found in Hamlin et al (2020), where the HSR label was not associated with a change in breakfast cereal choice among adolescents [54].…”
Section: The Impact Of Fopls On Food Choice and Consumer Behaviorsupporting
confidence: 78%
“…A macro-simulation study that used the Preventable Risk Integrated Model (PRIME), estimated the impact of FOPLs on deaths from NCDs, suggesting that they could delay or prevent 3.4% of cases on average, with some differences between labels, and the greater results were achieved by Nutri-Score and HSR [83]. However, in different settings, HSR has been criticized for not being particularly useful in influencing consumer choice, especially in purchasing sugar-rich products [54].…”
Section: The Impact Of Fopls On Dietary Patternmentioning
confidence: 99%
“…At the very least, this suggests that HSR’s real-world effectiveness is contingent on it providing accurate and visible information on unhealthy products for consumers. It also suggests potential for future research to explore how this HSR’s capacity to ‘steer’ consumers away from these products could be enhanced, for example by incorporating red colour into the HSR graphic of products that receive a low rating [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%